TEORI MOTIVASI ABRAHAM H. MASLOW DAN IMPLIKASINYA DALAM KEGIATAN BELAJAR MATEMATIKA - Zebua, Try Gunawan (RANGE: Jurnal Pendidikan Matematika, 2021)
ABSTRACT One of the famous Motivation Theory is Abraham H. Maslow's Motivation Theory which is also referred to as Abraham H. Maslow's Motivation Theory or Maslow's Hierarchy of Needs Theory. Students' Mathematics Learning Achievement and Mathematics Learning Outcomes can be categorized as low, so a solution needs to be given by implying Abraham H. Maslow's Motivation Theory. The research method used in this research is Literature Study, where the researcher analyzes Abraham H. Maslow's Motivation Theory directly from Abraham H. Maslow's book entitled Motivation and Personality (translation of Achmad Fawaid and Maufur, the publisher of Cantrik Pustaka), then the researcher analyzes the impact of the theory. if it is implied in mathematics learning activities. Abraham H. Maslow's Motivation Theory in the first stage can be applied in mathematics learning activities by providing food and drink to students, the second stage can be applied by making students safe in mathematics learning activities, the third stage can be applied by establishing communication between teachers and students, The fourth stage can be applied in a way that there is mutual respect between teachers and students and fellow students, and the fifth stage can be applied by providing opportunities for students to express opinions in discussion activities. By implying Abraham H. Maslow's Motivation Theory can influence or improve students' Mathematics Learning Achievement and Mathematics Learning Outcomes. Keywords: Abraham H's Motivation Theory, Maslow, Dream, Learning Mathematics.